Gender Trespass and Masculine Privilege:: “Male Trouble” in Jack Hodgins’s Spit Delaney’s Island - Lesk, Andrew; Stolar, Batia (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2001)
A question posed in the story "Separating," — 'Where is the dividing line?' — acts as a starting point from which to explore the dividing line between various sex/gender constructs in the collection of stories that makes up Jack Hodings's Split Delaney's Island. The differences between the ostensibly natural and the culturally constructed are explored in order to understand ideas and expressions of desire that are present in the stories in the collection. Using various recent theories concerning margins, peripheries, and centres to inform a reading of the stories in Split Delaney's Island allows one to explore and challenge what traditionally counts as viable notions of sexuality and desire. In particular, such an approach challenges notions of masculinity, male desire, and sexuality, or some combination of these. Hodgins's work challenges critics to expand and refigure modes of permissible literary criticism in Canada, particularly involving meanings of gender and masculinity.